Exploring Local Wisdom: Analysis of Non-Verbal Communication Skills in Cirebon Traditional Mask Dance Audiences - Wahyuningsih, Olyvia; Salsabila, Irma Nuraeni; Hernawan, Adam; Savandha, Septien Dwi; Karsa, Aldo Hermaya Aditiya Nur (Ridwan Institute, 2024)
This research delves into the intriguing realm of mask dance and its role as a nonverbal communication medium for audiences in Cirebon. By examining dance skills such as movement, rhythm, expression, level, and floor patterns, the study aims to unravel the profound impact of this art form. A qualitative approach and descriptive research design are adopted to achieve this, allowing for a comprehensive exploration of the performance form and the far-reaching effects of mask dance. The research findings promise to provide profound insights into the significance of dance in preserving local culture. By shedding light on the intricate nuances of mask dance, this study contributes to a deeper understanding of the art's value and cultural implications. Not only does it enhance our understanding of the art form itself, but it also holds practical implications for researchers and stakeholders in the field. The knowledge gleaned from this research equips researchers and stakeholders with a more profound appreciation and recognition of the richness embedded within the Cirebon mask dance. It serves as a testament to the power of dance as a nonverbal form of communication, capable of transcending language barriers and conveying messages that resonate with audiences on a profound level. This research serves as a valuable resource, providing a foundation upon which future studies and initiatives can build, further enhancing the preservation and promotion of local art and culture.